The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/10598405211071002
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Stress – A Focus Group Interview Study Among Swedish Adolescents During the COVID-19 Pandemic

Abstract: Adolescence can be a stressful period in life. The period contains challenges associated with the transition from childhood to adulthood (body changes, changes in interpersonal relationships, and identity changes). The aim was to investigate experiences of stress among adolescents in addition to stress related to the COVID-19 pandemic. Focus group interviews (n = 8) were conducted with girls (n = 22) and boys (n = 19) aged 13–15 in southern Sweden. The transcribed interviews were analyzed with qualitative cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
(56 reference statements)
2
6
0
Order By: Relevance
“…Previous experiences of stress were from junior high school, when the students reported that stress was difficult to manage. This is in line with most other studies showing that school-related work was the main cause of stress even at younger ages [ 5 , 7 , 9 , 10 ]. In upper secondary school, the adolescents experienced that the pressure from school decreased compared to junior high school.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Previous experiences of stress were from junior high school, when the students reported that stress was difficult to manage. This is in line with most other studies showing that school-related work was the main cause of stress even at younger ages [ 5 , 7 , 9 , 10 ]. In upper secondary school, the adolescents experienced that the pressure from school decreased compared to junior high school.…”
Section: Discussionsupporting
confidence: 93%
“…The interview guide has been used previously among 13–15-year-old adolescents [ 5 ] and 10–12-year-old children [ 4 ]. Examples of questions are “What do you think when you hear the word stress?” and “Can you describe situations when stress has been good/bad?” The research project on stress in children and adolescents started before the pandemic.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many have chosen lock downs (a shutdown of the entire society). On March 18, 2020, one-hundred seven countries chose national school closure, which affected approximately 862 million children and young people in these counties and corresponds to half the world's students ( Viner et al, 2020 ). In the United Nations (2020) report from August 2020, 1,600 million children in 190 countries were affected.…”
mentioning
confidence: 99%